SCHOOL LEADERSHIP IN TEACHER RESOURCE QUALITY DEVELOPMENT PLANNING - Rahmat Soe’oed; James Marpaung; Zaenab Hanim (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This study aims to describe the role of principal leadership in planning the development of the quality of teacher resources at SMP Negeri 2 Sebulu Kutai Kartanegara. Related to the role of principal leadership in planning, implementing, evaluating planned programs in developing the quality of teacher resources. This research uses a qualitative approach with this type of research, namely a case study. Data collection techniques through observation, interviews and documentation. Data analysis used the Miles & Huberman model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results showed: (1) planning for the development of the quality of teacher resources was carried out by deliberation in internal meetings; (2) the form of developing the quality of teacher resources, namely the implementation of workshops, training, seminars and advanced education levels; (3) evaluating by conducting academic supervision; (4) the role of the principal as: (a) educator; (b) managers; (c) administrator; (d) supervisors; (e) leader (f) innovator; and (g) motivators. Based on the results of interviews with three informants about the principal's leadership in planning the development of the quality of teacher resources, the principal as a leader has tried to carry out according to procedures in determining planning, namely by involving stakeholders in internal school meetings. In the implementation process, it is carried out in accordance with the procedure, all the steps taken by the principal and the teacher are to begin with the formation of a school development team, each school development team is given a mandate according to its capacity.